Electromagnetic flowmeters in multiphase flows - Krafft, Rainer (Cranfield University, 1993)
The response of an Electromagnetic Flowmeter to a secondary, nonconducting phase in a continuous conducting phase is investigated. Experiments are carried out on a commercial 2" Foxboro flowmeter with sinusoidal mains field excitation and point electrodes. The main aspects which are looked for are the change in flow signal and transformer signal. A mathematical model is developed to simulate the effect of the nonconducting phase in. the form of single spherical particles. The model also allows one to alter the electrode geometry. A second flowmeter is designed to incorporate an improved electrode and coil geometry as well as a newly designed signal processing unit. In a series of experiments, the predictions of the theoretical model have been mostly verified.